Effect of merger and acquisition on acquirer banks in the Middle East and North Africa Region - Sindi, Sameer Mohammed A (2019)
The trends associated with merger and acquisitions in the Middle East and North Africa region have changed in the last decade and increased significantly. Most of the existing merger and acquisitions studies tend to focus on the effects of merger and acquisitions in banking in developed countries, and limited studies have examined the effects of merger and acquisitions in banking in developing countries such as the Middle East and North Africa countries. In addition, there is considerable debate among many researchers regarding the benefits afforded to economic efficiency especially through growth in both scale and scope as a result of merger and acquisitions activities. Therefore, a comprehensive examination of the effects of merger and acquisitions on acquirer banks in the Middle East and North Africa region has been undertaken in this study by investigating and analysing four main effects: the short term effect, long term effect, efficiency effect and risk effect. Different methods were employed to achieve the objectives of this study. The event study method examined the short term effect, using financial ratios to investigate the long term effect, data envelope analysis to examine the efficiency effect, and applying total risk and market risk to measure the risk effect of merger and acquisitions on acquirer banks in the Middle East and North Africa region. The findings from the study found that some banks experienced positive or negative abnormal returns during merger and acquisition announcements in the region. However, these positive or negative abnormal returns were not statistically significant. Although, the financial ratio results for all acquirer banks indicated that five ratios were negatively affected, and two ratios were positively affected as a result of merger and acquisition deals in the region. However, these positive or negative effects were not statistically significant. All three efficiency levels (revenue, cost, and profit) in banks changed following merger and acquisition deals. The results from conducting both the parametric and non-parametric tests indicated the difference in profit, revenue and cost efficiency of the acquirer banks were not statistically significant. Similarly, the mean of the total relative risk ratio and beta for all acquirer banks suggested that the total relative risk ratio experienced a slight increase following merger and acquisition deals whereas, beta experienced a slight decrease after merger and acquisition deals. Although similar to the above findings, the results from the parametric and non-parametric tests indicated that the difference in the total relative risk ratio and the beta of the acquirer banks were not statistically significant. Therefore, based on the overall findings and results, this study concludes that the merger and acquisition effects (i.e., the short-term, long-term, efficiency and risk) did not play a significant role in the acquirer banks following merger and acquisition deals in the Middle East and North Africa region. The most prominent factor affecting the outcome of merger and acquisition deals related to the agency problem which could explain why some banks in developing countries remain interested in banking merger and acquisition deals. The empirical findings of this study are expected to contribute significantly to the existing knowledge regarding merger and acquisitions in the banking industry in the Middle East and North Africa region, particularly for policymakers, managers and stakeholders of banks. Additionally, the findings and results of this study will also assist various stakeholders in the industry such as investors, creditors, employees, bankers and others in understanding the importance of merger and acquisitions in the Middle East and North Africa region.